PENGARUH SAFETY CULTURE TERHADAP IMPLEMENTASISAFETY MANAGEMENT SYSTEM DI UNIT PERAWATAN PESAWAT UDARA SEKOLAH TINGGI PENERBANGAN INDONESIA - Novyanto Widadi; Afiya Krysna Bashyari (Politeknik Penerbangan Indonesia Curug, 2019)
The Aircraft Maintenance Unit does not yet know how much the Safety Culture and Safety Management System has been built. This study aims to examine the implementation of Safety Culture, the implementation of the Safety Management System, and the effect of Safety Culture on the Safety Management System. This quantitative study obtained data from questionnaires, observations and documentation. Based on the results of the questionnaire, it was concluded that the Safety Culture condition was in the good category (82.5%) and the Safety Management System was in the good category (82.75%). The gap analysis data shows that the achievement of Safety Management System implementation reached 79.58%. Safety Culture and Safety Management System have a strong relationship level (0.7694). Safety Culture contributed 59.19%